The role of adenosine A1 receptors in the nucleus accumbens during morphine withdrawal - YANANLI, HASAN RACİ; GÖREN, MEHMET ZAFER (WILEY, 2020)
Opioids are effective analgaesic agents, but serious adverse effects such as tolerance and withdrawal contribute to opioid dependence and limit their use. Opioid withdrawal is a common occurrence in human opiate addicts that is not life-threatening. Studies have shown that the mesocorticolimbic system, especially the nucleus accumbens, is an important region in drug addiction and adenosine receptors play a modulatory role in the mechanism of action of drug dependence and withdrawal. The aim of this study was to investigate the effects of the selective A(1) receptor agonist CPA (N-6-cyclopentyladenosine) on withdrawal symptoms, and the concentration of dopamine and noradrenaline in the nucleus accumbens and locomotor activity behaviour during naloxone-precipitated withdrawal in morphine-dependent rats. The local administration of CPA (1.5, 3.0, and 6.0 mmol/L bilateral 250 nL) into the nucleus accumbens decreased the Gellert-Holtzman withdrawal scale, and increased concentrations of dopamine and noradrenaline in the same region during naloxone-induced withdrawal. Our findings suggest that administration of the A(1) receptor agonist significantly decreased withdrawal behaviours and increased dopamine and noradrenaline concentrations in opioid withdrawal in a dose-dependent manner. These results demonstrate that adenosine receptors should be examined as a potential mechanism that could be exploited for the treatment of morphine withdrawal.
Keywords: adenosine; CPA; dopamine; morphine; noradrenaline; nucleus accumbens; ADENOSINE A(1) RECEPTORS; D-ASPARTATE RECEPTOR; SYNAPTIC-TRANSMISSION; MEDIATED MODULATION; OPIATE WITHDRAWAL; PREFRONTAL CORTEX; DOPAMINE RELEASE; A(2A) RECEPTORS; GABA RELEASE; RAT